All-optical spin access via a cavity-broadened optical transition in on-chip hybrid quantum photonics - Antoniuk, Lukas; Lettner, Niklas; Ovvyan, Anna; Haugg, Simon; Klotz, Marco; Gehring, Helge; Wendland, Daniel; Agafonov, Viatcheslav N.; Pernice, Wolfram; Kubanek, Alexander (Physical review applied, 2024)
Hybrid quantum photonic systems connect classical photonics to the quantum world and promise to deliver efficient light-matter quantum interfaces while leveraging the advantages of both, the classical and the quantum, subsystems. However, combining efficient, scalable photonics and solid-state quantum systems with desirable optical and spin properties remains a formidable challenge. In particular, the access to individual spin states and coherent mapping to photons remains unsolved for hybrid systems. In this paper, we demonstrate all-optical initialization and readout of the electron spin of a negatively charged silicon-vacancy center in a nanodiamond coupled to a silicon nitride photonic crystal cavity. We characterize relevant parameters of the coupled emitter-cavity system and determine the silicon-vacancy center’s spin-relaxation and spin-decoherence rate. Our results mark a key step towards the realization of a hybrid spin-photon interface based on silicon nitride photonics and the silicon-vacancy center’s electron spin in nanodiamonds with potential use for quantum networks, quantum communication, and distributed quantum computation.
Online veröffentlich: 16. Mai 2024
Gesehen am 21.01.2025